A rare case report of a typical variant ossifying fibromyxoid tumor (OFMT), located in the retroauricular perimastoid region. (2018) - Varakliotis, Theodoros; Bellocchi, Gianluca; Eibenstein, Alberto; Acquaviva, Gilberto; Casorati, Francesco
Highlights: Ossifying fibromyxoid tumor of soft parts (OFMT) has an uncertain histopathogenesis and is characterized by a peripheral bone shell embedded in a fibromyxoid matrix. Folpe and Weiss proposed a classification with "typical", "atypical" and "malignant" variants. The exam revealed a right perimastoid mass formation (2.2 × 1.2 × 2 cm) with an oval morphology, extended right to the back of the external ear canal, characterized by the predominant calcific component. The cytoplasm is described as a poorly eosinophilic, arranged to form solid nests and cords immersed in abundant collagenous and/or myxoid stroma, interposed in a mature irregularly shaped trabecular bone. Considering that it is extremely rare, and the possibility of local metastasis especially for the malignant type, we believe that more studies are required for this "enigmatic" tumor. Abstract: Introduction: Ossifying fibromixoid tumor of soft parts (OFMT) is a rare soft tissue and bone tumor. In its classic form, is considered benign, nevertheless aggressive clinical behaviour tumors with a different cytoarchitectural features of a malignant variant, have been described.The classification contains "typical", "atypical" and "malignant" variants. Methods: A CT ear scan without contrast enhancement was carried out (October 2015), with coronal, sagittal and 3D reconstructions. It was decided the removal of the neoformation with a simple dissection. Results: In this report, we present a case of a typical variant OFMT localized in the retroauricular perimastoid region, with mastoid bone cortex not involved. Conclusions: Considering the extreme rarity of this "enigmatic" tumor which displays an uncertain line of differentiation, renders the differential diagnosis a true challenge.